A non-canonical autophagy-dependent role of the ATG16L1T300A variant in urothelial vesicular trafficking and uropathogenic Escherichia coli persistence. Issue 3 (4th March 2019) - Wang, Caihong; Bauckman, Kyle A.; Ross, Adam S. B.; Symington, Jane W.; Ligon, Marianne M.; Scholtes, Gael; Kumar, Akhil; Chang, Hao-Wei; Twentyman, Joy; Fashemi, Bisiayo E.; Xavier, Ramnik J.; Mysorekar, Indira U.
ABSTRACT: 50% of Caucasians carry a Thr300Ala variant (T300A) in the protein encoded by the macroautophagy/autophagy gene ATG16L1 . Here, we show that the T300A variant confers protection against urinary tract infections (UTIs), the most common infectious disease in women. Using knockin mice carrying the human T300A variant, we show that the variant limits the UTI-causing bacteria, uropathogenic Escherichia coli (UPEC), from establishing persistent intracellular reservoirs, which can seed UTI recurrence. This phenotype is recapitulated in mice lacking Atg16l1 or Atg7 exclusively in the urothelium. We further show that mice with the T300A variant exhibit urothelial cellular abnormalities, including vesicular congestion and aberrant accumulation of UPK (uroplakin) proteins. Importantly, presence of the T300A variant in humans is associated with similar urothelial architectural abnormalities, indicating an evolutionarily conserved impact. Mechanistically, we show that the reduced bacterial persistence is independent of basal autophagic flux or proinflammatory cytokine responses and does not involve Atg14 or Epg5 . However, the T300A variant is associated with increased expression of the small GTPase Rab33b ; RAB33B interacts with ATG16L1, as well as other secretory RABs, RAB27B and RAB11A, important for UPEC exocytosis from the urothelium. Finally, inhibition of secretory RABs in bladder epithelial cells increases intracellular UPEC load. Together, our results reveal that UPEC selectively utilize genes important for autophagosome formation to persist in the urothelium, and that the presence of the T300A variant in ATG16L1 is associated with changes in urothelial vesicle trafficking, which disrupts the ability of UPEC to persist, thereby limiting the risk of recurrent UTIs. Abbreviations : 3-PEHPC: 3-pyridinyl ethylidene hydroxyl phosphonocarboxylate; ATG: autophagy; ATG16L1: autophagy related 16 like 1; BECs: bladder epithelial cells; dpi: days post infection; hpi: hours post infection; IF: immunofluorescence; IL1B: interleukin 1 beta; IL6: interleukin 6; MAP1LC3B/LC3B: microtubule-associated protein 1 light chain 3 beta; MVB: multivesicular bodies; T300A: Thr300Ala; TNF: tumor necrosis factor; QIR(s): quiescent intracellular reservoir(s); siRNA: short interfering RNA; UPEC: uropathogenic Escherichia coli ; UTI(s): urinary tract infection(s); TEM: transmission electron microscopy; WT: wild type